2011
DOI: 10.1308/003588411x12851639107070
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between ultrasonography and histology in the search for gallstones

Abstract: This study suggests that, despite an evolution in the resolution of ultrasound imaging, there has not been a corresponding improvement in sensitivity. There is a false positive rate of 16% which remains unchanged since the early 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…Comment: Abdominal ultrasonography is the imaging of choice in patients with upper abdominal quadrant pain. Its accuracy for detecting gallbladder stones is in excess of 95% [234][235][236]. Older patients with atypical abdominal pain, immunocompromised patients with unclear site of infection, or patients with bacteremia suspicious for an abdominal septic focus may also be evaluated by abdominal ultrasound for the presence of (complicated) gallstones.…”
Section: Which Imaging Modality Is Most Appropriate To Diagnose Gallsmentioning
confidence: 99%
“…Comment: Abdominal ultrasonography is the imaging of choice in patients with upper abdominal quadrant pain. Its accuracy for detecting gallbladder stones is in excess of 95% [234][235][236]. Older patients with atypical abdominal pain, immunocompromised patients with unclear site of infection, or patients with bacteremia suspicious for an abdominal septic focus may also be evaluated by abdominal ultrasound for the presence of (complicated) gallstones.…”
Section: Which Imaging Modality Is Most Appropriate To Diagnose Gallsmentioning
confidence: 99%
“…Indeed, the false positive rate for ultrasound in the search for gallstones can be as high as 16% as demonstrated by ahmed and Diggory. 12 our study found that after laparoscopic cholecystectomy for acalculous gallbladder disease 66% (37/56) of patients experienced complete resolution of their symptoms of pain in terms of severity, frequency and relation to food. This group was entirely cured of their symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Regarding the comparison between the variables of the gallbladder and biliary tract of sonographic reports with the same surgical variables measured macroscopically by the team of surgeons, it was found that USG has high values ​​for sensitivity, consistency and positive predictive value for the presence/ identification/absence of stones, 98.8%, 96.7% and 97.8% respectively. In the literature, the sensitivity value for stones identification ranged from 85-98% 1 , 5 , 26 . Regarding the number of gallstones (single or multiple) the USG has agreed in 82.7%, with negative predictive value in 89.1% and specificity in 87.7%.…”
Section: Discussionmentioning
confidence: 99%